Analysis of the syrB and syrC genes of Pseudomonas syringae pv. syringae indicates that syringomycin is synthesized by a thiotemplate mechanism. - Zhang, J H (1995)
The syrB and syrC genes are required for synthesis of syringomycin, a lipodepsipeptide phytotoxin produced by Pseudomonas syringae pv. syringae, and are induced by plant-derived signal molecules. A 4,842-bp chromosomal region containing the syrB and syrC genes of strain B301D was sequenced and characterized. The open reading frame (ORF) of syrB was 2,847 bp in length and was predicted to encode an approximately 105-kDa protein, SyrB, with 949 amino acids. Searches of databases revealed that SyrB shares homology with members of a superfamily of adenylate-forming enzymes involved in peptide antibiotic and siderophore synthesis in a diverse spectrum of microorganisms. SyrB exhibited the highest degree of overall similarity (56.4%) and identity (33.8%) with the first amino acid-activating domain of pyoverdin synthetase, PvdD, of Pseudomonas aeruginosa. The N-terminal portion of SyrB contained a domain of approximately 600 amino acids that resembles the amino acid-activating domains of thiotemplate-employing peptide synthetases. The SyrB domain contained six signature core sequences with the same order and spacing as observed in all known amino acid-activating domains involved in nonribosomal peptide synthesis. Core sequence 6 of SyrB, for example, was similar to the binding site for 4'-phosphopantetheine, a cofactor required for thioester formation. The syrC ORF (1,299 bp) was located 175 bp downstream of the syrB ORF. Analysis of the transcriptional and translational relationship between the syrB and syrC genes demonstrated that they are expressed independently. The syrC ORF was predicted to encode an approximately 48-kDa protein product of 433 amino acids which is 42 to 48% similar to a number of thioesterases, including fatty acid thioesterases, haloperoxidases, and acyltransferases, that contain a characteristic GXS (C) XG motif. In addition, a zinc-binding motif was found near the C terminus of SyrC. The data suggest that SyrB and SyrC function as peptide synthetases in a thiotemplate mechanism of syringomycin biosynthesis.